Consumer Perception towards Fresh Meat and Processed Meat Consump tion in the city of Tirupati, India (Indian Journal of Animal Production and Management, 2025)
A study was conducted to understand consumer perception towards meat and meat  products consumption in Tirupati city. The city of Tirupati has witnessed a sharp rise  in the households which is evident with the rapid expansion of the city outskirts by  means of real-estate developments. This pose a greater scope for meat startups to be  established in the rapidly developing city. A total of 200 respondents were randomly  selected and were interviewed. Data were collected using pre- tested structured interview  schedule by personal interviews. The study group comprised of 76 males & 124 females.  The educational background of respondents was found to vary between uneducated  to PG & PhD level. The overall mean age of the consumers was found to be (33.5) of  which majority (45%) belong to middle age group. The study revealed that most of the  consumers ate meat for taste (67%) and health benefits (33%) and usually consume meat  twice in a week (51%). The most preferred meat was chicken (53%), followed by chevon  (21%), sea foods (fish, prawns 16%) and other meat (10%). Gravy type meat products  were most preferred, followed by biryani (19%) and fried meat products (15%). Most  of the consumers (63%) opined that meat have good cholesterol (HDL) and (28%) as  bad cholesterol (LDL) whereas (9%) opined as both. The willingness to purchase chilled/ frozen meat was very low (5%). The acceptance of the respondents towards processed  meat products such as pickles (80%), comminuted meat products at (20%) respectively.  The majority of the respondents (82%) believed that over consuming of meat leads to  heart problems and other diseases. Unfortunately (78%) of the respondents have no idea  about what kind of vitamins and minerals are present in meat. Most of the consumers  said that ideal method for cooking is boiling (78%) and frying (22%). Only (40%) of  the respondents have awareness about zoonotic diseases. Food safety has emerged as  an important global issue with international trade and public health implications.  The current study also revealed that most of the respondents have no idea about laws  pertaining to food safety. The. results indicated that most respondents consume meat  for taste and as a cultural tradition. However, majority of the consumers lack scientific  backdrop about fresh meat and processed meat, which further can be overcome by  conducting extensive awareness programmes and advertisements by the government  agencies and entrepreneurs in the meat trade. The consumer awareness about scientific  handling of meat can safeguard their health and also pave a way for huge investments in  the meat startups in the developing cities.
Keywords: Consumer; consumption pattern; meat; food safety